An approach for assessing the effects of porous materials on controlling the tire cavity resonance noise. (October 2022) - Wan, Cheng; Zheng, Chang-Jun; Bi, Chuan-Xing; Zhang, Yong-Bin
Abstract: Pasting porous material on the inner surface of a tire is an effective means to mitigate the tire cavity resonance noise. However, its performance is highly related to the material properties and geometry. This paper proposes an eigenvalue analysis approach based on the multi-domain boundary element method (MBEM) to evaluate this performance and further help determine the optimal parameters of the porous material lining in a tire. In this approach, the porous material is equivalent to a fluid, and the MBEM is used to model the sound fields in the air and equivalent fluid domains inside the tire cavity, based on which the eigenvalue analysis is conducted and the associated nonlinear eigenproblem is solved by using a contour integral method. The accuracy and validity of the proposed method are first verified by using a two-dimensional tire model with analytical solution, and then testified by comparing with the experimental results of a real tire lined with porous materials with different flow resistivities, thicknesses and widths. Furthermore, the effects of porous materials with different parameters are investigated based on the proposed method and the optimal parameters are suggested for a typical three-dimensional tire model.